3D Numerical Simulation of Landslides for the Full High Waste Dump Using SPH Method. (26th February 2021) - Cao, Chunhui; Feng, Jili; Tao, Zhigang
Abstract : Waste dump that is generally composed of a large number of loose geotechnical materials is prone to landslides under external loads. In this work, the smoothed particle hydrodynamics (SPH) method combined with the Mohr–Coulomb model is used to study the dynamic characteristics of the landslides that occurred in the waste dump during the failure process. A benchmark test is firstly conducted to verify the effectiveness of the SPH model. Then, taking the Nanfen full high waste dump with a vertical drop of 300 m in Benxi City, China, as an example, the most dangerous section is selected to establish the SPH numerical model for the waste dump landslides, and the overall dynamic process of the landslides is simulated. The simulation results show that the particles in the middle and upper of the slope have larger potential energy, and their sliding distance is larger. On the contrary, the sliding distance of particles in the lower of the slope is smaller. The particles' sliding distance decreases as the depth increases in the vertical direction of both shoulder and middle of the slope. The particles undergo a process of first acceleration and then deceleration. The sliding distance is in good agreement with the field survey result, and the landslides profile is basically consistent with the actual one. The sensitivity analysis of different particle numbers shows that the number of particles has little effect on the numerical results. The SPH method can vividly reproduce the dynamic process of the landslides in the full high waste dump. The evaluation of the sliding characteristics and risk impact range can provide the key parameters and basis for the prevention and control of the landslides in the full high waste dump and ensure the safety of the mine life cycle.